Pengaruh Dana Pihak Ketiga, Kecukupan Modal dan Risiko Kredit terhadap Profitabilitas LPD Desa Adat Jimbaran Periode Tahun 2013-2017 - Kadek Jedicia Valentina Yo; A.A. Sri Purnami; A. A. Gede Agung Parameswara (Warmadewa Economic Development Journal (WEDJ), 2020)
To answer the questions posed in this study, the method of the Classic Assumption Test, Multicollinearity Test, Heterocedasticity Test, Autocorrelation, Multiple Linear Regression Analysis, t Test, Determination Coefficient, and the third F Test, capital adequacy and credit risk to the profitability of Credit Institutions Desa (LPD) Adat Jimbaran Village, and through the data collection method used is a multiple linear regression data analysis technique method. Thus it can be made multiple linear regression as follows: DPK variables are positive and not significant to profitability, if deposits increase then profitability will increase, and vice versa. The capital adequacy variable has a positive and not significant effect on profitability, if capital adequacy increases the profitability increases, so that the opposite variable credit adequacy has a negative and not significant effect on profitability, if credit credit increases then profitability will increase, and vice versa.